Integration of complete chloroplast genome sequences with small amplicon datasets improves phylogenetic resolution in Acacia - Williams, A.; Miller, J.; Small, I.; Nevill, Paul; Boykin, L. (2016)
Combining whole genome data with previously obtained amplicon sequences has the potential to increase the resolution of phylogenetic analyses, particularly at low taxonomic levels or where recent divergence, rapid speciation or slow genome evolution has resulted in limited sequence variation. However, the integration of these types of data for large scale phylogenetic studies has rarely been investigated. Here we conduct a phylogenetic analysis of the whole chloroplast genome and two nuclear ribosomal loci for 65 Acacia species from across the most recent Acacia phylogeny. We then combine this data with previously generated amplicon sequences (four chloroplast loci and two nuclear ribosomal loci) for 508 Acacia species. We use several phylogenetic methods, including maximum likelihood bootstrapping (with and without constraint) and ExaBayes, in order to determine the success of combining a dataset of 4000 bp with one of 189,000 bp. The results of our study indicate that the inclusion of whole genome data gave a far better resolved and well supported representation of the phylogenetic relationships within Acacia than using only amplicon sequences, with the greatest support observed when using a whole genome phylogeny as a constraint on the amplicon sequences. Our study therefore provides methods for optimal integration of genomic and amplicon sequences.